Respostas
respondido por:
40
Reaolviendo :
(x+3)^5
a= X.
b = 3
n = 5
p + 1 = 5 => p = 5 - 1 => p = 4
Formula :
<><><><><>
T (p + 1) = ( n ; p ) a^n - p . b^p
T (4 + 1) = ( 5 ; 4 ) X^5-4 * 3^4
T (5) = ( 5 ; 4 ) X^1 * 3^4
T (5) = ( 5 ; 4 ) X * 81
T (5) = 5 * X * 81
T(5) = 405X
Resposta o quinto termo e 450X....
(x+3)^5
a= X.
b = 3
n = 5
p + 1 = 5 => p = 5 - 1 => p = 4
Formula :
<><><><><>
T (p + 1) = ( n ; p ) a^n - p . b^p
T (4 + 1) = ( 5 ; 4 ) X^5-4 * 3^4
T (5) = ( 5 ; 4 ) X^1 * 3^4
T (5) = ( 5 ; 4 ) X * 81
T (5) = 5 * X * 81
T(5) = 405X
Resposta o quinto termo e 450X....
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás